Delta Opioid Receptor Activation with Delta Opioid Peptide [d-Ala2, d-Leu5] Enkephalin Contributes to Synaptic Improvement in Rat Hippocampus against Global Ischemia. (31st August 2021) - Zhang, Guangming; Lai, Zelin; Gu, Lingling; Xu, Kejia; Wang, Zhenlu; Duan, Yale; Chen, Huifen; Zhang, Min; Zhang, Jun; Zhao, Zheng; Wang, Shuyan
Global cerebral ischemia induced by cardiac arrest usually leads to poor neurological outcomes. Numerous studies have focused on ways to prevent ischemic damage in the brain, however clinical therapies are still limited. Our previous studies revealed that delta opioid receptor (DOR) activation with [d-Ala2, d-Leu5] enkephalin (DADLE), a DOR agonist, not only significantly promotes neuronal survival on day 3, but also improves spatial memory deficits on days 5-9 after ischemia. However, the neurological mechanism underlying DADLE-induced cognitive recovery remains unclear. This study first examined the changes in neuronal survival in the CA1 region at the advanced time point (day 7) after ischemia/reperfusion (I/R) injury and found a significant amelioration of damaged CA1 neurons in the rats treated with DADLE (2.5 nmol) when administered at the onset of reperfusion. The structure and function of CA1 neurons on days 3 and 7 post-ischemia showed significant improvements in both the density of the injured dendritic spines and the basic transmission of the impaired CA3-CA1 synapses following DADLE treatment. The molecular changes involved in DADLE-mediated synaptic modulation on days 3 and 7 post-ischemia implied the time-related differential regulation of PKCα-MARCKS on the dendritic spine structure and of BDNF- ERK1/2-synapsin I on synaptic function, in response to ischemic/reperfusion injury as well as to DADLE treatment. Importantly, all the beneficial effects of DADLE on ischemia-induced cellular, synaptic, and molecular deficits were eliminated by the DOR inhibitor naltrindole (2.5 nmol). Taken together, this study suggested that DOR activation-induced protective signaling pathways of PKCα-MARCKS involved in the synaptic morphology and BDNF-ERK-synapsin I in synaptic transmission may be engaged in the cognitive recovery in rats suffering from advanced cerebral ischemia.